Using targeted vouchers and health equity funds to improve access to skilled birth attendants for poor women: a case study in three rural health districts in Cambodia - Ir, Por (BioMed Central, 2010)
BACKGROUND: In many developing countries, the maternal mortality ratio remains high with huge poor-rich inequalities. Programmes aimed at improving maternal health and preventing maternal mortality often fail to reach poor women. Vouchers in health and Health Equity Funds (HEFs) constitute a financial mechanism to improve access to priority health services for the poor. We assess their effectiveness in improving access to skilled birth attendants for poor women in three rural health districts in Cambodia and draw lessons for further improvement and scaling-up. METHODS: Data on utilisation of voucher and HEF schemes and on deliveries in public health facilities between 2006 and 2008 were extracted from the available database, reports and the routine health information system. Qualitative data were collected through focus group discussions and key informant interviews. We examined the trend of facility deliveries between 2006 and 2008 in the three health districts and compared this with the situation in other rural districts without voucher and HEF schemes. An operational analysis of the voucher scheme was carried out to assess its effectiveness at different stages of operation. RESULTS: Facility deliveries increased sharply from 16.3% of the expected number of births in 2006 to 44.9% in 2008 after the introduction of voucher and HEF schemes, not only for voucher and HEF beneficiaries, but also for self-paid deliveries. The increase was much more substantial than in comparable districts lacking voucher and HEF schemes. In 2008, voucher and HEF beneficiaries accounted for 40.6% of the expected number of births among the poor. We also outline several limitations of the voucher scheme. CONCLUSIONS: Vouchers plus HEFs, if carefully designed and implemented, have a strong potential for reducing financial barriers and hence improving access to skilled birth attendants for poor women. To achieve their full potential, vouchers and HEFs require other interventions to ensure the supply of sufficient quality maternity services and to address other non-financial barriers to demand. If these conditions are met, voucher and HEF schemes can be further scaled up under close monitoring and evaluation.